Altérité et « latinité » aux États-Unis - Emmanuelle Le Texier (Revue LISA)
In the US, the complex interaction with the “Other” is based on identity discourses that question the definition of national identity. Identity discourses are simultaneously used by and for Mexicans and people of Mexican origin. In the relation between “minorities” and “majority”, it is fundamental to study how ethnic categories are imposed upon the “Other” because this explains both power relations and the formation of “Otherness”. The “Foreigner” is not always the “Other”. He might also be one of the minority group who no longer corresponds to the model of the “Self”. As a consequence, the concept of the “Foreigner” has repercussions on the minority group itself. “Latinidad” is part of this process. This article explores the competitive and fragmented identities which coexist in a US urban ethnic enclave in San Diego, California. This analysis of the dynamics behind “latinidad” shows that identity specificities account not only for inclusion in or exclusion from the national group, but also demonstrate the heterogeneity of the “Latino” community.